STUDI EKSPERIMENTAL KAPASITAS SAMBUNGAN TIPE PELAT TUNGGAL PADA SAMBUNGAN BALOK ANAK DENGAN BAUT - , BAEHAKI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A single plate connection type makes a gusset plate that overlaps on web beam so itâs makes the axis of gusset plate is not aligned with the axis beam. This condition produces eccentricity on the forces which is transfered from gusset plate to the web of beam. Because of the eccentricity and insufficient stifness of the gusset plate, it occurs twisting behaviour and it reduces the capacity of single plate connection. Issues that are going to be showed are, the capacity of single plate connection type which is used on connection of beam with bolt, the failure behavior, and the calculation methods that can predict accuratly the capacity of single plate connection type in this study. This research shows the result of experimental, analitical, and numerical studies that suppose to resolve the issues, and it explains the negative impact of the use single plate connection type. Three full scale tests of a single plate connection type were conducted to examine the effects of two main test parameter which are eccentricity in connection and stiffness of gusset plate. Moreover the cocentric loading condition will be discussed based on finite element analysis by using ABAQUS. Average connection capacity from the whole result of eksperimental test is 9,39 ton. Thas result is close to the capacity value from cross sectional analytical methode in the combination of torsional and shear capacity. The average ratio of test-to-predict is 1,43. The failure behavior of three specimen are twisting failure that occur gusset palte. Moreover the cocentric loading condition could increase connection capacity.